2016
DOI: 10.1007/s13318-016-0335-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Drug–Drug Pharmacokinetic Interaction Potential of Sucralfate with Other Drugs: Review and Perspectives

Abstract: Sucralfate, a complex of aluminium hydroxide with sulfated sucrose, forms a strong gastrointestinal tract (GIT) mucosal barrier with excellent anti-ulcer property. Because sucralfate does not undergo any significant oral absorption, sucralfate resides in the GIT for a considerable length of time. The unabsorbed sucralfate may alter the pharmacokinetics of the oral drugs by impeding its absorption and reducing the oral bioavailability. Because of the increased use of sucralfate, it was important to provide a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Sucralfate, another commonly prescribed gastroprotectant, is a complex of sulfated sucrose and aluminum 16,17 . It protects the gastrointestinal mucosal barrier from gastric acid damage by providing a physical barrier, as well as increasing local bicarbonate production to buffer its effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sucralfate, another commonly prescribed gastroprotectant, is a complex of sulfated sucrose and aluminum 16,17 . It protects the gastrointestinal mucosal barrier from gastric acid damage by providing a physical barrier, as well as increasing local bicarbonate production to buffer its effects.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, there have been concerns about the coadministration of gastroprotectants with antithrombotics, particularly omeprazole with clopidogrel 15 . In addition, sucralfate, a complex of aluminum hydroxide with sulfated sucrose, has strong gastrointestinal mucosal barrier properties and could interfere with the absorption of other orally administered drugs including antithrombotics 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…Sucralfate is another common class of drug co-administered with NSAIDs for its gastroprotective effects. Sucralfate is thought to have multiple mechanisms of action, including mucosal synthesis, formation of a protective mucosal barrier, buffering of hydrogen ions and encouraging luminal secretion of PGE 2 leading to increased epithelial cell restitution [ 77 ]. Pharmacokinetic studies investigating the drug interaction between sucralfate and NSAIDs in humans suggest that co-administration of the drugs may lead to delayed absorption of NSAIDs, however no studies investigating drug interaction on pharmacokinetic parameters in horses have been published [ 77 ].…”
Section: Pathologymentioning
confidence: 99%
“…Uncontrolled diabetes, advanced kidney diseases, and sensitivity to the drug are the only contraindications for its use. 1,[3][4][5] Even though exact sucralfate in-vivo mechanisms of action remain unknown, in-vitro studies have suggested the seven following mechanisms: 1. inhibition of bacterial activity; 2. reducing oxygen-free radical generation; 3. the effects on arachidonic acid metabolism and increasing prostaglandin release by activating macrophages, cyclooxygenase activity, synthesis, and release of leukotriene C4; 4. decreasing cell apoptosis; 5. enhancing growth factor bioavailability; 6. the effects as a site-protective agent through providing a physical barrier; 7. the effects on tissue growth, regeneration, and repair: facilitating blood flow, cell proliferation, and repair via binding growth factors to tissues 6,7 (Figure 1). In addition to systemic sucralfate, a topical form of drug efficacy has been evaluated in several mucocutaneous indications as clinical and case studies.…”
Section: Introductionmentioning
confidence: 99%